2020
DOI: 10.1002/lary.29141
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Vestibular Schwannoma Volume With Facial Nerve Outcomes After Surgical Resection

Abstract: Objective: To explore the relationship between tumor size and facial nerve outcomes following vestibular schwannoma (VS) resection. Study Design: Single institutional retrospective chart review of all adult patients with untreated sporadic VS who underwent surgical resection from 2008 to 2018 with preoperative magnetic resonance imaging (MRI) and 1 year of follow-up. The primary outcome measure was facial nerve outcome as assessed by the House-Brackmann facial nerve grading system. Results: One hundred sixty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…Many tumor parameters have been investigated as potential predictors of FN outcome. Larger tumor volume has consistently been associated with poor FN outcomes (3,5,7,12,19,23). Similarly, our analysis found that larger tumor volume was associated with poor short- and long-term FN function.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Many tumor parameters have been investigated as potential predictors of FN outcome. Larger tumor volume has consistently been associated with poor FN outcomes (3,5,7,12,19,23). Similarly, our analysis found that larger tumor volume was associated with poor short- and long-term FN function.…”
Section: Discussionsupporting
confidence: 76%
“…Microsurgical resection remains a favorable option for large tumors with brainstem compression, hydrocephalus, growing tumors, or symptomatic patients. Recent literature suggests management of VS has increasingly favored observation or radiation in place of microsurgery, likely reflecting a lower tolerance for cranial neuropathy, particularly facial nerve paralysis in VS treatment outcomes (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…The goal of VS surgery is complete resection while preserving neurological function, which is challenging ( 1 , 4 , 5 , 25 , 26 ). For large VSs, the RS approach is preferred when hearing preservation is required.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to pursue surgical management instead of radiotherapy or active surveillance is multifactorial and largely depends on features including age, comorbidity, initial tumor size, rate of growth, hearing status, and patient preference. The mortality rate in patients surgically managed is very low and affords the opportunity to shift focus to other relevant clinical outcomes, such as recurrence-free survival, growth-free survival, surgical complications, facial nerve functioning, hearing preservation, and quality of life …”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate in patients sur-gically managed is very low and affords the opportunity to shift focus to other relevant clinical outcomes, such as recurrencefree survival, growth-free survival, surgical complications, facial nerve functioning, hearing preservation, and quality of life. [4][5][6] Patient symptom presentation is a fundamental characteristic of the patient with VS and likely relates to the pathophysiologic characteristics of the tumor. Symptoms at presentation include cardinal symptoms, such as hearing loss, vestibular dysfunction, facial numbness, tinnitus, and headaches.…”
mentioning
confidence: 99%